Inhibition of SDF-1/CXCR4 Axis to Alleviate Abnormal Bone Formation and Angiogenesis Could Improve the Subchondral Bone Microenvironment in Osteoarthritis. (29th May 2021) - Qin, Hanjun; Zhao, Xingqi; Hu, Yan Jun; Wang, Shengnan; Ma, Yunfei; He, Siying; Shen, Ke; Wan, Haoyang; Cui, Zhuang; Yu, Bin
Abstract : The pathogenesis of the osteoarthritis (OA) is complex. Abnormal subchondral bone metabolism is an important cause of this disease. Further understanding on the pathology of the subchondral bone in OA may provide a new therapy. This research is about to investigate the role of SDF-1 in the subchondral bone during the pathological process of OA. In vitro, Transwell was used to test the migratory ability of bone marrow mesenchymal stem cells (BMSCs) and human umbilical vein endothelial cells (HUVECs). Western blot presented the protein level after SDF-1 treatment in BMSCs and HUVESs. Alizarin red was used to assess the ability of osteogenic differentiation. To inhibit SDF-1 signaling pathway in vivo, AMD3100 (SDF-1 receptor blocker) was continuously delivered via miniosmotic pump for 4 weeks in mice after performing anterior cruciate ligament transaction surgery. Micro-CT, histology staining, immunofluorescence, immunohistochemistry, and TRAP staining were used to assess the role of SDF-1 on osteogenesis and angiogenesis in the subchondral bone. Our results showed that SDF-1 could recruit BMSCs, activate the p-ERK pathway, and enhance osteogenic differentiation. SDF-1 promoted the ability of proliferation, migration and tube formation of HUVECs by activating the ERK and AKT signaling pathways. In an animal study, inhibition of SDF-1/CXCR4 axis could significantly reduce subchondral osteogenesis differentiation and H-type vessel formation. Furthermore, the AMD3100-treated group showed less cartilage destruction and bone resorption. Our research shows that SDF-1 alters the microenvironment of the subchondral bone by promoting osteoid islet formation and abnormal H-type angiogenesis in the subchondral bone, resulting in articular cartilage degeneration.